2021
DOI: 10.1093/gji/ggab420
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning-based earthquake locations reveal the seismogenesis of the 2020 Mw 5.0 Qiaojia, Yunnan earthquake

Abstract: Summary A moment magnitude (Mw) 5.0 earthquake hit Qiaojia, Yunnan, China on May 18, 2020. Its hypocenter is only approximately 20 km away from the Baihetan reservoir, the second largest hydropower station in China. The Baihetan Reservoir is located at the junction of multiple fault zones on the eastern boundary of the Sichuan-Yunnan rhombic block, an area with high background seismic activity. The Baihetan Reservoir was planned to be impounded in April 2021 and the MW 5.0 earthquake occurred du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, the PhaseNet phase picker comes with a training data set containing ∼700,000 seismic waveform samples collected from northern California more than 30 years (W. Zhu & Beroza, 2019), and it has significantly improved the accuracy of S ‐wave arrivals picking compared to the STA/LTA method. In addition, the PhaseNet method has been widely applied to many earthquake location studies (e.g., Liu et al., 2020; Tan et al., 2021; R. Wang et al., 2020; L. Zhou et al., 2022) and magmatic system studies in Mayotte and Hawaii (Retailleau et al., 2022; W. Zhu et al., 2022). Nevertheless, some weak seismic phases may be missed out when using just a single method (Figures S1 and S2 in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the PhaseNet phase picker comes with a training data set containing ∼700,000 seismic waveform samples collected from northern California more than 30 years (W. Zhu & Beroza, 2019), and it has significantly improved the accuracy of S ‐wave arrivals picking compared to the STA/LTA method. In addition, the PhaseNet method has been widely applied to many earthquake location studies (e.g., Liu et al., 2020; Tan et al., 2021; R. Wang et al., 2020; L. Zhou et al., 2022) and magmatic system studies in Mayotte and Hawaii (Retailleau et al., 2022; W. Zhu et al., 2022). Nevertheless, some weak seismic phases may be missed out when using just a single method (Figures S1 and S2 in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the PhaseNet method has been widely applied to many earthquake location studies (e.g., Liu et al, 2020;Tan et al, 2021;R. Wang et al, 2020;L. Zhou et al, 2022) and magmatic system studies in Mayotte and Hawaii (Retailleau et al, 2022;.…”
Section: Phase Pickingmentioning
confidence: 99%
“…The three notable deep learning pickers are a general phase generalized seismic phase detection (GPD) (Ross et al, 2018), PhaseNet (Zhu and Beroza, 2019), and the current state-of-the-art Earthquake Transformer (EQT) (Mousavi et al, 2020). These deep-learning-based pickers have improved the quantity and quality of earthquake detection, and phase picks in various studies (Liu et al, 2020;Wang et al, 2020;Xiao et al, 2021;Zhou et al, 2021). Moreover, a new study evaluating the performance of deep learning pickers indicated that the Earthquake Transformer could be considered the most reliable picker for local earthquakes within an epicentral distance of about 350 km (Münchmeyer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many ML algorithms are built to (1) automatically perform complex prediction task; (2) create a representation that approximates numerical simulations or captures relationships; (3) reveal new patterns, structures, or relationships from data (Bergen et al, 2019). ML algorithms are powerful in many different seismological tasks, including but not limited to waveform classification and earthquake detection (Li et al, 2018;Perol et al, 2018;Kong et al, 2019;Mousavi et al, 2019bMousavi et al, , 2020Beroza et al, 2021;Johnson et al, 2021), phase picking and association (Li et al, 2018;Meier et al, 2019;Zhu et al, 2019a;Liu et al, 2020;Mousavi et al, 2020;Walter et al, 2021), source location and characterization (Perol et al, 2018;Mousavi and Beroza, 2019;Ren et al, 2020;van den Ende and Ampuero, 2020;Kuang et al, 2021;Münchmeyer et al, 2021a;Zhou et al, 2021), earthquake early warning (Li et al, 2018;Münchmeyer et al, 2021b), and many others.…”
Section: Introductionmentioning
confidence: 99%